Analysis of step drawdown pumping test data (a modified approach) - Qaium, Dhali Abdul; Gupta, Ashim Das; Tawatchai Tingsanchali; Huynh, Ngoc Phien; French Government (Bangkok : Asian Institute of Technology, 1983)
The procedure for the analysis of step drawdown pumping test data for a confined, homogeneous, isotropic and infinite areal extent has been developed considering the effect of previous pumping rates. The cases of pumping test with equal step duration and unequal step duration are dealt with separately. An attempt is made to compare the results obtained from this analysis with the results obtained from the existing methods to analyze the step drawdown pumping test data. The proposed Model evaluates the unknown parameters for both the well loss component and the aquifer loss component. To determine the values of the unknown parameters, the general equation. s/Q = k log ta + k log k' + CQ P-1 which express the relationship between specific drawdown, discharge rate and time of a step pumping test data containing the unknown parameters are solved in two steps. Thus the above equation is linearized. First, the parameter 'k ' is determined from the plotting of specific drawdown vs . log of adjusted time as the relationship between the variables is linear for each step since well loss component is constant (for a particular step). And once 'k' is known, the relationship between the variables becomes linear (for log-log plotting in case of first approach and assuming ' P' value in case of second approach) and thus, linear regression analysis procedure is applied to solve the equations of step pumping test. A computer program , 'MODIFIED-FIRST', developed to solve the step pumping test data for the case of equal step duration minimizes the difference between actual drawdown and regenerated drawdown using linear regression analysis considering the aquifer parameters as decisive variables. In the case of unequal step duration , the computer code 'MODIFIED-SECOND' minimizes the difference between the actual difference of specific drawdowns for two adjacent steps and regenerated difference of specific drawdowns for those two steps considering the exponent of discharge of well loss component as decisive variables. Linear regression analysis is also used in this program. Computer programs have also been developed for five existing methods to solve the step puming test data. Four sets of step pumping test data have been analyzed by the proposed method and by the five existing methods. The results obtained from this study indicate that prediction of drawdown is excellent if the effects of previous pumping on present pumping rate is considered and the exponent of discharge is considered as an unknown parameter. The exponent of discharge, ' P' is more important than the effects of previous pumping on present pumping rate to predict drawdown in a pumping well. A method to analyses the step pumping test data considering 'P' as an unknown parameter and considering the effects of previous pumping on present pumping rate is suggested.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Wells -- Testing; Aquifers -- Testing